Antimicrobial susceptibility testing and antibiotic consumption results from 16 hospitals in Viet Nam: The VINARES project 2012–2013 - Dung Tien Viet Vu; Thi Thuy Nga; Ulf Rydell; Lennart E. Nilsson; Linus Olson; Mattias Larsson; Håkan Hanberger; Marc Choisy; Tuyet Trinh Dao; H. Rogier van Doorn; Vān Kính Nguyễn; Vu Trung Nguyen; et al. (2019)
To establish a hospital-based surveillance network with national coverage for antimicrobial resistance (AMR) and antibiotic consumption in Viet Nam.A 16-hospital network (Viet Nam Resistance: VINARES) was established and consisted of national and provincial-level hospitals across the country. Antimicrobial susceptibility testing results from routine clinical diagnostic specimens and antibiotic consumption data in Defined Daily Dose per 1000 bed days (DDD/1000 patient-days) were prospectively collected and analysed between October 2012 and September 2013.Data from a total of 24 732 de-duplicated clinical isolates were reported. The most common bacteria were: Escherichia coli (4437 isolates, 18%), Klebsiella spp. (3290 isolates, 13%) and Acinetobacter spp. (2895 isolates, 12%). The hospital average antibiotic consumption was 918 DDD/1000 patient-days. Third-generation cephalosporins were the most frequently used antibiotic class (223 DDD/1000 patient-days, 24%), followed by fluoroquinolones (151 DDD/1000 patient-days, 16%) and second-generation cephalosporins (112 DDD/1000 patient-days, 12%). Proportions of antibiotic resistance were high: 1098/1580 (69%) Staphylococcus aureus isolates were methicillin-resistant (MRSA); 115/344 isolates (33%) and 90/358 (25%) Streptococcus pneumoniae had reduced susceptibility to penicillin and ceftriaxone, respectively. A total of 180/2977 (6%) E. coli and 242/1526 (16%) Klebsiella pneumoniae were resistant to imipenem, respectively; 602/1826 (33%) Pseudomonas aeruginosa were resistant to ceftazidime and 578/1765 (33%) to imipenem. Of Acinetobacter spp. 1495/2138 (70%) were resistant to carbapenems and 2/333 (1%) to colistin.These data are valuable in providing a baseline for AMR among common bacterial pathogens in Vietnamese hospitals and to assess the impact of interventions.